INCREASING THE PHYSICAL CONDITION OF YOUNG PEOPLE FROM CLUJ NAPOCA THROUGH MODERN MEANS (Fiep Bulletin - online, 2020)
Problem statement: We believe that new sports are just as effective for developing physical fitness as well as well-established sports. These are practiced by young people because they are more spectacular, easy to practice and fun. This study consists of an experiment done with students for a period of 7 months, between October 2016 and April 2017, in some gyms from Cluj-Napoca. The intervention program consisted of carrying out programs from the following disciplines: Breakdance, Capoeira, Kangoo Jumps and Free running.Study hypothesis: We’ve started this study supposing that by applying these training programs specific to Breakdance, Kangoo Jumps, Free running and Capoeira, the participating subjects in the experiment will improve their speed, pace, thrust, general coordination, dynamic balance, joint mobility and muscle elasticity.References: With this paper, we try to make a contribution to the development and dissemination of these four emerging new sports in Romania. We want to achieve this goal by scientifically proving how they help improve the speed of movement, rhythm, thrust, dynamic balance, overall coordination and mobility. Research design: Two groups took part in our research: one who participated in the experiment and the control group. The dependent variable is represented in our experiment by the subjects and their level of physical condition considering the speed of movement, rhythm, thrust, general coordination, dynamic balance and mobility. For each discipline, there were 6 subjects: 3 boys and 3 girls aged between 15-25 years old. In our case, the independent variable is the training program applied to the subjects. The training consisted of 3 sessions/week of 90 minutes for Breakdance; 3 sessions/week of 60 minutes for Kangoo Jumps; 3 sessions/week of 120 minutes for Free running; 3 sessions/week of 90 minutes for Capoeira. Conclusions: After 7 months of research, documentation, creation and measurement, we came to the conclusion that our hypothesis was confirmed. The newly emerging disciplines contributed significantly to improving the speed of movement, rhythm, thrust, general coordination, dynamic balance and mobility. Not in all cases the improvement was significant.